2020
DOI: 10.1186/s40792-020-00900-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transhiatal surgery for an epiphrenic esophageal diverticulum derived from a jackhammer esophagus: a case report

Abstract: Background: An esophageal diverticulum is rare and is frequently associated with esophageal motility disorders. Jackhammer esophagus is also rare, is characterized by esophageal hypercontraction, and comprises 4.1% of esophageal motility disorders. Here, we report a case of a patient successfully treated by laparoscopic transhiatal surgery for an epiphrenic esophageal diverticulum derived from a jackhammer esophagus diagnosed with highresolution manometry (HRM). Case presentation: The patient was a 78-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Even though the transthoracic approach is a safe approach, decreased respiratory function might be an adverse event, especially in patients with compromised lung function. Currently, several reports have illustrated the feasibility of the laparoscopic trans‐hiatal approach and the benefits over the transthoracic approach, particularly in an initial antireflux procedure after myotomy 5,6 . Fujinaga et al suggested that a trans‐hiatal approach is possible to address an ED located within 10 cm from the esophagogastric junction 5 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though the transthoracic approach is a safe approach, decreased respiratory function might be an adverse event, especially in patients with compromised lung function. Currently, several reports have illustrated the feasibility of the laparoscopic trans‐hiatal approach and the benefits over the transthoracic approach, particularly in an initial antireflux procedure after myotomy 5,6 . Fujinaga et al suggested that a trans‐hiatal approach is possible to address an ED located within 10 cm from the esophagogastric junction 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several reports have illustrated the feasibility of the laparoscopic trans‐hiatal approach and the benefits over the transthoracic approach, particularly in an initial antireflux procedure after myotomy 5,6 . Fujinaga et al suggested that a trans‐hiatal approach is possible to address an ED located within 10 cm from the esophagogastric junction 5 . However, a tailored combined laparoscopic and thoracoscopic approach was suggested to address an ED located at the mid‐thoracic level of the esophagus or an ED with a large neck 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations